Meta-analysis of Protocolized Goal-directed Hemodynamic Optimization for the Management of Severe Sepsis and Septic Shock in the Emergency Department - Charles R. Wira; Kelly Dodge; John Sather; James Dziura (Western Journal of Emergency Medicine, 2014)
Introduction: To perform a meta-analysis identifying studies instituting protocolized hemodynamic optimization in the emergency department (ED) for patients with severe sepsis and septic shock.